Complications of Tonsillectomy and Management - ., Arifullah; Hassan, Sayed Zafar; Muhammad, Ghulam (Journal of Gandhara Medical and Dental Science, 2015)
OBJECTIVE: The objective of the study was to determine the complications of tonsillectomy and management of these the complications. MATERIAL AND METHODS: The study was Randomized controlled trial conducted from 1st January 2008 to 31 December 2009 (of two year duration) at ENT Department Khyber Teaching Hospital, Peshawar. Total 2156indoorpatientsof all age ad both sex, underwent tonsillectomy were included in the study. RESULTS: In my study all of the 2156 patients underwent tonsillectomy were having pain in which 1176 patients (56%) with mild to moderate pain and 980 patients (44%) with severe pain, 1274 patients (59%) nausea and vomiting, 129 patients (7%) bleeding, 19 patients (<1%) airway obstruction, 273 patients fever and infection, 17 patients (<1%) pneumonia, 126 patients (6%) dehydration, and injury to surrounding structure like teeth injury in 105 patients (5%), temporary uvular or tongue edema in 367 patients (17%), and other rare complications (<1%) like temporomandibularjoint dislocation in 7 patients, Grisel’s syndrome in 5 patients, atlanto-axial joint subluxation in 1 patient and glossopharyngeal nerve damage in 3 patients. CONCLUSION: Though tonsillectomy is a routine and safe surgery can result in morbid complications and can cause death. By adopting pre and per-op basic steps can minimize the complications of tonsillectomy.